2022
DOI: 10.1007/s11010-022-04456-7
|View full text |Cite
|
Sign up to set email alerts
|

Serine-Arginine Protein Kinase 1 (SRPK1): a systematic review of its multimodal role in oncogenesis

Abstract: Alternative splicing is implicated in each of the hallmarks of cancer, and is mechanised by various splicing factors. Serine-Arginine Protein Kinase 1 (SRPK1) is an enzyme which moderates the activity of splicing factors rich in serine/arginine domains. Here we review SRPK1’s relationship with various cancers by performing a systematic review of all relevant published data. Elevated SRPK1 expression correlates with advanced disease stage and poor survival in many epithelial derived cancers. Numerous pre-clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Current approaches to exploiting SRPK, CLK and DYRK kinase families for therapy SRPK, CLK, DYRK, and sub-family HIPK have been associated with several disease indications, with potential therapeutic strategies either discussed or being pursued. Disease areas include viral infection and replication [193,[281][282][283][284], tumour angiogenesis [285,286], and other aspects of tumour growth and biology [2,113,[287][288][289]. The diverse roles of DYRKs in cancer have been extensively reviewed elsewhere [126,[290][291][292][293].…”
Section: Therapeutic Potential Of Srpk Clk and Dyrk Kinase Families I...mentioning
confidence: 99%
“…Current approaches to exploiting SRPK, CLK and DYRK kinase families for therapy SRPK, CLK, DYRK, and sub-family HIPK have been associated with several disease indications, with potential therapeutic strategies either discussed or being pursued. Disease areas include viral infection and replication [193,[281][282][283][284], tumour angiogenesis [285,286], and other aspects of tumour growth and biology [2,113,[287][288][289]. The diverse roles of DYRKs in cancer have been extensively reviewed elsewhere [126,[290][291][292][293].…”
Section: Therapeutic Potential Of Srpk Clk and Dyrk Kinase Families I...mentioning
confidence: 99%
“…These genes play important roles in the occurrence and development of tumors, and the abnormal activity of SRPK1 may affect the function of these genes. Research has found that SRPK1 is aberrantly expressed in both the tissue and cells of gliomas, while no abnormal expression has been observed in normal glioma cells [21]. Silencing SRPK1 has been shown to induce cisplatin resistance [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that SRPK1 is aberrantly expressed in both the tissue and cells of gliomas, while no abnormal expression has been observed in normal glioma cells [21]. Silencing SRPK1 has been shown to induce cisplatin resistance [21,22]. Under normoxic and moderately hypoxic conditions, knocking down SRPK1 inhibits the malignant progression of glioma cells [21,22], induces apoptosis in glioma cells [21,23], and suppresses AKT/E1F4E phosphorylation [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations